2021
DOI: 10.1080/13607863.2021.1947967
|View full text |Cite
|
Sign up to set email alerts
|

Centrally-acting anticholinergic drugs– associations with mortality, hospitalisation and cognitive decline following dementia diagnosis in people receiving antidepressant and antipsychotic drugs

Abstract: C. (2021). Centrally-acting anticholinergic drugs-associations with mortality, hospitalisation and cognitive decline following dementia diagnosis in people receiving antidepressant and antipsychotic drugs. Aging and Mental Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…48 Also, there were significant association between antipsychotic drugs and cognitive decline in same dementia cohort regardless of centrally acting anticholinergic effect. 49 Some drug groups such as α1 antagonist, antihistamines, N-methyl-D-aspartate receptor antagonists, and psychotropic sedatives were associated with accelerated cognitive decline in dementia patients. 50 However, we could not find any studies that specifically explored the cognitive changes associated with the use of anticholinergic drugs in patients with DLB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Also, there were significant association between antipsychotic drugs and cognitive decline in same dementia cohort regardless of centrally acting anticholinergic effect. 49 Some drug groups such as α1 antagonist, antihistamines, N-methyl-D-aspartate receptor antagonists, and psychotropic sedatives were associated with accelerated cognitive decline in dementia patients. 50 However, we could not find any studies that specifically explored the cognitive changes associated with the use of anticholinergic drugs in patients with DLB.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that drugs used in the treatment of urinary incontinence and depression, cause poor results in terms of cognitive decline in dementia patients due to their centrally acting anticholinergic effects 48 . Also, there were significant association between antipsychotic drugs and cognitive decline in same dementia cohort regardless of centrally acting anticholinergic effect 49 . Some drug groups such as α1 antagonist, antihistamines, N -methyl- d -aspartate receptor antagonists, and psychotropic sedatives were associated with accelerated cognitive decline in dementia patients 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants and antipsychotics were also examined separately to investigate their effects on outcomes in dementia. Studies found that the influence of anticholinergic burden did not increase mortality with antidepressants 32,37 or antipsychotics 37 in people with dementia and if anything, a reverse association was found with antidepressants. 37 So contrary to expectation, tricyclic antidepressants were safer than antidepressants with low anticholinergic burden.…”
Section: The Evidencementioning
confidence: 98%
“…the Anticholinergic Cognitive Burden Scale, 25 the Anticholinergic Risk Scale, 26 the Anticholinergic Drug Scale, 27 and the Drug Burden Index) 28 . The use of drugs with anticholinergic activity and high ACB is linked to adverse events such as reduced physical functioning, falls, reduced quality of life, hospitalisation, and mortality among PwD 29–34 . Reduction of anticholinergic drug use and ACB in PwD has therefore been highlighted as a research priority 14…”
Section: Introductionmentioning
confidence: 99%
“…28 The use of drugs with anticholinergic activity and high ACB is linked to adverse events such as reduced physical functioning, falls, reduced quality of life, hospitalisation, and mortality among PwD. [29][30][31][32][33][34] Reduction of anticholinergic drug use and ACB in PwD has therefore been highlighted as a research priority. 14 Following diagnosis, PwD will be predominantly managed and supported within primary care settings.…”
Section: Introductionmentioning
confidence: 99%